Women Entrepreneurs in Focus: Trends, Insights, and Future Research Pathways - Clarissa, Fiona; Marvianta, YB Andre (AIBPM Publisher, 2025)
This study explores the dynamics of women’s digital entrepreneurship, focusing on the themes of empowerment, survival strategies, and inclusive economic development. The research goal is to analyze the trends, barriers, and emerging themes in this field using bibliometric methods. The findings reveal that while empowerment and digital transformation have facilitated women's involvement in entrepreneurship, challenges such as gender stereotypes, limited access to capital, and network exclusion persist. Resilience, family support, and financial literacy are essential for the survival of women-led businesses, particularly in micro-enterprises. Additionally, digital entrepreneurship plays a critical role in financial inclusion and poverty alleviation, offering opportunities for marginalized groups to engage in the global economy. The study highlights the need for policies to foster an inclusive ecosystem and to address intersectional factors affecting success. Future research should focus on women’s experiences and the impact of digital tools on business success. These findings have practical implications for creating more equitable environments for women entrepreneurs.